2009
DOI: 10.1021/am9000858
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Nanotube-Based Materials for Protein Crystallization

Abstract: We report on the first use of carbon-nanotube based films to produce crystals of proteins. The crystals nucleate on the surface of the film. The difficulty of crystallising proteins is a major bottleneck in the determination of the structure and function of biological molecules. The crystallisation of two model proteins and two medically relevant proteins was studied. Quantitative data on the crystallisation times of the model protein lysozyme are also presented. Two types of the nanotube film, one made with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
86
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 29 publications
1
86
0
Order By: Relevance
“…The metastable conditions for heterogeneous crystallization of proteins reported in the literature were used as the starting point in the current work 2,16,34 . To isolate the influence of the surface porosity on …”
Section: Effect Of Nucleant Surface Porosity On Protein Crystallizationmentioning
confidence: 99%
“…The metastable conditions for heterogeneous crystallization of proteins reported in the literature were used as the starting point in the current work 2,16,34 . To isolate the influence of the surface porosity on …”
Section: Effect Of Nucleant Surface Porosity On Protein Crystallizationmentioning
confidence: 99%
“…Adsorption or immobilization of proteins and peptides on solid substrates plays an important role in many biotechnological applications, such as biocatalysis, biosensing, biomaterials, surface-induced protein crystallization, and drug delivery systems [1][2][3][4][5][6][7][8][9][10]. As a matter of fact, the success of these applications strongly depends on the activities of the adsorbed proteins and peptides which are determined by their conformations on substrates.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to templates was pioneered by Chayen and co-workers [2][3][4], who showed that materials with disordered nanoscale pitted surfaces can act as ''universal'' nucleation agents in the sense that they induce the nucleation of crystals of many different proteins. See Refs.…”
mentioning
confidence: 99%